Activity of ceftazidime/avibactam against problem Enterobacteriaceae and Pseudomonas aeruginosa in the UK, 2015–16. (8th December 2017) - Livermore, David M; Meunier, Danièle; Hopkins, Katie L; Doumith, Michel; Hill, Robert; Pike, Rachel; Staves, Peter; Woodford, Neil
Abstract: Background: Ceftazidime/avibactam combines an established oxyimino-cephalosporin with the first diazabicyclooctane β-lactamase inhibitor to enter clinical use. We reviewed its activity against Gram-negative isolates, predominantly from the UK, referred for resistance investigation in the first year of routine testing, beginning in July 2015. Methods: Isolates were as received from referring laboratories; there is a bias to submit those with suspected carbapenem resistance. Identification was by MALDI-TOF mass spectroscopy, and susceptibility testing by BSAC agar dilution. Carbapenemase genes were sought by PCR; other resistance mechanisms were inferred using genetic data and interpretive reading. Results: Susceptibility rates to ceftazidime/avibactam exceeded 95% for: (i) Enterobacteriaceae with KPC, GES or other Class A carbapenemases; (ii) Enterobacteriaceae with OXA-48-like enzymes; and (iii) for ESBL or AmpC producers, even when these had impermeability-mediated ertapenem resistance. Almost all isolates with metallo-carbapenemases were resistant. Potentiation of ceftazidime by avibactam was seen for 87% of ceftazidime-resistant Enterobacteriaceae with 'unassigned' ceftazidime resistance mechanisms, including two widely referred groups of Klebsiella pneumoniae where no synergy was seen between cephalosporins and established β-lactamase inhibitors. Potentiation here may be a diazabicyclooctane/cephalosporin enhancer effect. Activity was seen against Pseudomonas aeruginosa with derepressed AmpC, but not for those with efflux-mediated resistance. Conclusions: Of the available β-lactams or inhibitor combinations, ceftazidime/avibactam has the widest activity spectrum against problem Enterobacteriaceae, covering all major types except metallo-carbapenemase producers; against P. aeruginosa it has a slightly narrower spectrum than ceftolozane/tazobactam, which also covers efflux-type resistance.